The gardener's guide to cactus : the 100 best paddles, barrels, columns, and globes - Calhoun, Scott (Timber Press, 2012)
Here at last is a book that shows readers just how easy, hardy, and rewarding cactus can be for everyone - not just specialists. Scott Calhoun picks 100 of the best cactus available and shows how they can make striking additions to your garden or serve as dazzling container specimens